Meta-analysis Comparing Celecoxib with Diclofenac Sodium in Patients with Knee Osteoarthritis. Issue 2 (14th August 2020) - Huang, Hetao; Luo, Minghui; Liang, Haodong; Pan, Jianke; Yang, Weiyi; Zeng, Lingfeng; Liang, Guihong; Hou, Senrong; Zhao, Jinlong; Liu, Jun
Abstract: Objective: To compare the efficacy and safety of celecoxib and diclofenac sodium in patients with knee osteoarthritis (KOA). Methods: Clinical controlled trials (CCTs) and randomized controlled trials (RCTs) from online databases comparing the efficacy of celecoxib and diclofenac sodium in the treatment of KOA were retrieved. The main outcomes included the treatment effect, C-reactive protein (CRP) level, erythrocyte sedimentation rate (ESR), visual analog scale (VAS) score, and complication rate. The Cochrane risk of bias (ROB) tool in Review Manager 5.3.5 was used to assess methodological quality. Results: Twelve studies (N = 2, 350) were included in this meta-analysis. The meta-analysis indicated that celecoxib reduced pain more effectively than diclofenac sodium in patients with KOA, as evaluated by the VAS score. In addition, celecoxib has certain advantages in terms of better treatment effects and greater reductions in the ESR, CRP level, and complication rate. Conclusions: Celecoxib is superior to diclofenac sodium in the treatment of KOA. However, well-designed and high-quality RCTs are still needed.